What Factors Affect Debt Policy During the COVID-19 Outbreak? Case of Indonesia - Khanifah, Khanifah; Alif, Atiqullah Muhammad; Triyani, Agus; Setyahuni, Suhita Whini (Universitas Dian Nuswantoro Semarang, 2024)
This research examines the influence of free cash flow and company growth on debt policy at LQ 45 Companies on the Indonesia Stock Exchange in 2018-2021. We analyze 25 companies listed in the LQ-45 index during 2018-2021, with 100 firms-years observation in total. The sample is selected based on data availability using the purposive sample technique. We analyze the data using multiple regression analysis by using E-views software. The results indicate that Free cash flow has a positive effect on debt policy, while company growth does not affect debt policy. Our research contributes to the development of agency theory, and we use the new measurement of free cash flow. We also analyze the COVID-19 outbreak factors as a control variable, which becomes our important contribution to this research. Keywords:Free Cash FlowFirm GrowthDebt policy